PENGARUH PROFITABILITAS, PERTUMBUHAN PERUSAHAAN, DAN KEBIJAKAN HUTANG SEBAGAI DETERMINAN KEBIJAKAN DIVIDEN (STUDI PADA PERUSAHAAN MANUFAKTUR DI BEI PERIODE 2009-2011) - Hendra Hendra (Jurnal Akuntansi Bisnis, 2017)
The objective of this research is to identify the factors influencing the dividend policy of manufactured firms in Indonesian Stock Exchange period 2009 – 2011. This research using multiple regression with SPSS to test whether dividend policy is impacted by various variables, namely profitability (ROA), growth, and debt to equity ratio (DER). Based on statistical t test, ROA has significant influence to DPR. Based on statistical F test indicates that variables ROA, growth, and DER simultantly affect DPR on manufacturing companies listed in Indonesian Stock Exchange period 2009-2011.Key Words: Profitability (ROA), Growth, Debt to Equity Ratio (DER), Dividend Payout Ratio (DPR).